Teaching anti-discrimination attitudes through christian religious education in school - Sianipar, Desi; Sairwona, Wellem; Hasugian, Johanes Waldes; Ritonga, Nova; Zega, Yunardi Kristian (International Journal for Educational and Vocational Studies, 2021)
This study aims to figure the implementation of anti-discrimination Christian Religious Education (CRE) at school and various things that can significantly shape students' anti-discrimination attitudes. By using descriptive qualitative methods, namely by adopting the research procedures of Miles and Habermas and support of other literature, the researchers found that CRE at schools has a strategic place in teaching anti-discrimination attitudes toward students. In this regard, the contextual and biblical CRE curriculum design and learning model presented in the class can lead students to have attitudes that do not discriminate against one another. Teaching anti-discrimination attitudes through CRE can be done simultaneously. CRE teachers lay the foundation or instill Christian values that differences are the reality and how students can accept and appreciate differences. Those are strengthened by the application of the CRE curriculum that contains the topic of anti-discrimination and synergized learning models in which students can interact, communicate and relate in different realities.